Atypical neurological manifestations of dengue fever: a case series and mini review. Issue 1142 (8th September 2020) - Prabhat, Nandita; Ray, Sucharita; Chakravarty, Kamalesh; Kathuria, Heena; Saravana, Sukriya; Singh, Deependra; Rebello, Alex; Lakhanpal, Vikas; Goyal, Manoj Kumar; Lal, Vivek
Abstract: Background: In this mini review, we discuss some of the atypical neurological manifestations of dengue virus and attempt to bring them to attention to highlight the neurotropic property of the dengue virus. Methods: Cases were chosen from retrospective hospital and outpatient records of all patients seropositive for dengue who attended the neurology referral. Seven patients have been chosen as illustrative examples of dengue-associated neurological involvement. We discuss the various central and peripheral nervous system involvement of patients and discuss the relevant findings in them. Conclusion: Through this case series, we wish to highlight that the dengue virus can affect the nervous system at various targets, using multiple mechanisms of pathogenesis to generate a plethora of presentations. Hence, it is vital to be aware of its presentations to be able to diagnose dengue and treat it accordingly.